Divine Rites and Philosophy in Neoplatonism - Uždavinys, Algis (Acta Orientalia Vilnensia, 2003)
The essay deals with the problem of relationship between philosophy and ritual in late antiquity and attempts at showing that their close connections in Neoplatonism were determined not only by their common anagogic and mystic aim (homoiosis theo ideal), but also by distant origins of philosophy (in the form of traditional wisdom and hermeneutics: explanations of oracles, omens, riddles, rites, and events) from the integral unit of the cosmogonical and ‘seasonal’ (or rather metaphysical) ritual-and-myth complexes. Philosophy in her most ancient sense and under different names can be regarded as a semi-theurgic activity (framed by the particular world-model and the archaic conception of language) inseparable from the ‘divinely sanctioned’ lawmaking, ruling, healing and fighting. Even the much later syllogistic procedures and dialectical operations in some formal respect resembled ritualistic activities as if imitating certain ‘rhythmical’ patterns of proper behaviour in the context of the harmonious whole governed by the cosmic order or divine intelligence. Despite the well-known prejudices of the one-sided post-Enlightenment scholars against rites and liturgies, their own zealous pedantry and strive for classifications, rules, and systems could be interpreted in the light of ancient rituals (always strict and dogmatic in every detail) and sacrifices. The integration of some religious cults, symbols, and mysteries into the body of the post-lamblichean Neoplatonism cannot be regarded as an artificial undertaking directed against the supposed ‘rationalist purity’, itself partly invented by the Modern Western scholars. Rather it should be understood as the peacefull sumphonia of the maximally employed human reason and ineffable divine mysteries, including all practical and contemplative (or aesthetic) sides of life.